Analisis Kepuasan Wisatawan Terhadap Desa Wisata Halal dan Kreatif (Studi Wisata Puncak Ratu Desa Tebul Barat Kecamatan Pegantenan Kabupaten Pamekasan) - Ryas Tri Faturrohman; Nirma Kurriwati (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The purpose of this research is to find out and describe the satisfaction of Halal Tourism and Puncak Ratu Tourism Creative which is spread in the community or visitors in the development of Wsiata in Pamekasan Madura. This research was conducted using a qualitative research method with a case study approach. The sampling technique of this research is field research with the sampling technique used is accidental sampling. (1). In the perception indicator of facilities and infrastructure, there are several items that have not been maximized, namely, physical condition, cleanliness condition and satisfaction in use. (2) Perception indicators on tourism infrastructure have points that according to some informants have not been met, namely communication networks and waste disposal systems. Several informants also said they were satisfied. (3) Activity comfort indicators have points according to some informants that have not been fulfilled such as services, but other informants also said they were satisfied. (4) Satisfaction indicators for tourism activities according to some informants have points that have not been met, such as prayer facilities, but some informants also said they were satisfied with these indicators. Visitors stated that they were quite satisfied with all of the items offered on the tour, although there were some visitors who stated that they did not enjoy the Puncak Ratu Tour optimally. This does not prevent tourists from enjoying the panorama presented by Puncak Ratu Tourism.